2018
DOI: 10.1002/ar.23759
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Ends of Human Macula Densa Cells: Ultrastructural Investigation and Morphofunctional Correlations

Abstract: The morphology of the kidney macula densa (MD) has extensively been investigated in animals, whereas human studies are scanty. We studied the fine structure of human MD cells focusing on their apical and basal ends and correlating structure and function. The MD region was examined by transmission electron microscopy in six renal biopsies from patients with kidney disease. Ultrastructural analysis of MD cells was performed on serial sections. MD cells show two polarized ends. The apical portion is characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 36 publications
6
13
2
Order By: Relevance
“…The present ultrastructural data confirm our earlier findings reported in MD tissue from patients with glomerulonephritis (Cangiotti et al, 2018). In particular, they confirm that these cells are characterized by a dual differentiation due to the presence of two functionally different compartments.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The present ultrastructural data confirm our earlier findings reported in MD tissue from patients with glomerulonephritis (Cangiotti et al, 2018). In particular, they confirm that these cells are characterized by a dual differentiation due to the presence of two functionally different compartments.…”
Section: Discussionsupporting
confidence: 93%
“…The ultrastructural examination demonstrated that MD cells from healthy tissue are identical to those found in the glomerulonephritis patients that we described in a previous paper (Cangiotti et al, 2018) (Figure 2). In the present material, MD cells showed two polarized ends: the apical end was endowed with a primary cilium, whereas the basolateral end showed morphological features of a paracrine secretory cell.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations